Impact of depressive tendency on intertemporal decision-making in college students: the moderated mediation effects of perceived stress and self-control - Xie, Yutong; Wang, Zhen; Su, Danning; Li, Yuhang; Gao, Xinyu; Han, Jing; Xie, Bin (Frontiers in Psychiatry, 2026)
BackgroundThis study explored how depressive tendencies influence college students’ intertemporal decision-making, focusing on perceived stress and self-control as potential mechanisms to inform intervention strategies.MethodsAn online survey using CES-D, Perceived Stress Questionnaire, College Student Self-Control Scale, and Intertemporal Decision-making Scale collected 1,469 responses, with 436 valid ones from students scoring >10 on depressive tendency. Data were analyzed via descriptive, correlation, regression, and moderated mediation tests.ResultsResults showed depressive tendency positively correlated with intertemporal decision-making (r=0.55, p<0.01), positively predicted perceived stress (r=0.64, p<0.01), and negatively predicted self-control (r=-0.64, p<0.01). It directly predicted intertemporal decision-making (direct effect=0.23, 95% CI [0.07, 0.16]) and indirectly through perceived stress and self-control (indirect effect=0.29), forming a “depressive tendency - perceived stress - self-control - intertemporal decision-making” model.ConclusionsDepressive tendencies drive preference for immediate small rewards via heightened perceived stress and impaired self-control, suggesting interventions should focus on stress management and self-control training.